Faktor-Faktor Yang Memengaruhi Pemberian ASI Aksklusif Dalam PHBS Pada Tatanan Rumah Tangga Di Kelurahan Pelawi Kecamatan Babalan Kabupaten Langkat - Yusica Elisabeth Sirait; Ismail Efendy; Endang Maryanti (Pusat Riset dan Inovasi Nasional, 2024)
Exclusive breastfeeding is recommended in the form of breastfeeding for 6 months without other additional foods such as formula milk and other complementary foods. Although the number of mothers who have realized the importance of giving breast milk to their babies is increasing, they are still unable to breastfeed until 6 months. The purpose of the study was to determine the factors that influence exclusive breastfeeding in PHBS in the home setting in Pelawi Village, Babalan District, Langkat Regency.The research design used a quantitative method which was carried out by an analytical survey with a Cross Sectional Study approach. The population in this study were all mothers who had babies under 6 months of age as many as 98 mothers. The sample using the Total Sampling system is 98 mothers. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an effect of parity p = 0.017, knowledge p = 0.000, attitude p = 0.000, husband's support p = 0.013 and the role of health workers p = 0.000 on exclusive breastfeeding in PHBS in the home setting in Pelawi Village, Babalan District, Langkat Regency. While the most dominant factor is knowledge p = 0.000 and 95% CI = 7.002-677.067 with OR 68,851. The conclusion of this study is that there is an effect of parity, knowledge, attitude, husband's support and the role of health workers on exclusive breastfeeding in PHBS in the home setting in Pelawi Village, Babalan District, Langkat Regency. It is recommended for health workers to make efforts to approach with education and inform the benefits of exclusive breastfeeding.